2021
DOI: 10.1002/ar.24821
|View full text |Cite
|
Sign up to set email alerts
|

Standardization, objectification, and essence research of traditional Chinese medicine syndrome: A 15‐year bibliometric and content analysis from 2006 to 2020 in Web of Science database

Abstract: The standardization, objectification, and essence research of traditional Chinese medicine (TCM) syndrome influence the modernization and international development of TCM syndrome. A total of 253 relevant publications collected from the Web of Science Core Collection database from 2006 to 2020 were analyzed by bibliometric and content methods. The co‐occurrence analysis of countries, institutions, journals, authors, and keywords analysis were carried out by using Citespace software. The high‐yield institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The standardization, objectification, and essence of TCM studies are the foundation of TCM modernization and globalization. To understand the current state of knowledge in this area of research, Liu and Li (2023) analyzed TCM syndrome-related publications collected from the Web of Science Core Collection (WoSCC) database from 2006 to 2020. They found that the research hotspots of TCM in the past 15 years included six aspects, namely, the objectification research of the four TCM diagnostic methodologies, the application of omics technology in the field of TCM research, research on TCM syndrome evaluation scale, the application of metagenomic technology in TCM syndrome, the application of data mining technology in TCM syndrome differentiation, and the systematic research on the applications of TCM syndromes in chronic hepatitis B.…”
Section: The Research Of Tcm Syndrome Is Marching Towards Standardiza...mentioning
confidence: 99%
“…The standardization, objectification, and essence of TCM studies are the foundation of TCM modernization and globalization. To understand the current state of knowledge in this area of research, Liu and Li (2023) analyzed TCM syndrome-related publications collected from the Web of Science Core Collection (WoSCC) database from 2006 to 2020. They found that the research hotspots of TCM in the past 15 years included six aspects, namely, the objectification research of the four TCM diagnostic methodologies, the application of omics technology in the field of TCM research, research on TCM syndrome evaluation scale, the application of metagenomic technology in TCM syndrome, the application of data mining technology in TCM syndrome differentiation, and the systematic research on the applications of TCM syndromes in chronic hepatitis B.…”
Section: The Research Of Tcm Syndrome Is Marching Towards Standardiza...mentioning
confidence: 99%
“…However, despite the longevity of the practice in Asia, TCM has only recently become broadly discussed internationally (e.g., Han et al, 2023; Lam et al, 2019; Zhang & Li, 2021). The past 10 years have seen a rapid increase in the number of TCM syndrome papers published (Liu & Li, 2023), showing a growing increased interest around the world in TCM. Similarly, the onset of the COVID‐19 pandemic was also associated with a jump in TCM publications, which mainly focused on techniques and traditional herbs that may help to alleviate COVID‐19 symptoms, as a supplement to treatment by allopathic medicine (e.g., Da et al, 2021; Han et al, 2023).…”
Section: Figurementioning
confidence: 99%